O regime da estabilização da tutela antecipada - Flávia Pereira Hill (Revista Interdisciplinar de Direito, 2018)
The present study aims to analyse the so called “stabilization of preliminary injunctions”, a new instrument brought by the Brazilian Code of Civil Procedure of 2015, in order to reach the speedy trial principle. We seek to identify and critically examine the main sources of doubts and dissents, as a way to provide the adequate use of this brand new instrument.